Victimhood and Acknowledgement - Terhoeven, Petra (2018)
How does terrorism affect our picture of the history of terrorism then, if the victims are moved centre stage? If the focus is put on their suffering? The contributions to this edition of the European History Yearbook will examine such questions in a broad range of historical case studies and methods, including visual history.